Review Article: SNP rs11196205 Transcription Factor 7 Like 2 (TCF7L2) as a Metabolic Disorder Genetic Marker - Elsa Badriyya; Siti Fatimah Putri Hasyul (Genetikawan Muda Indonesia, 2022)
A metabolic disorder appears when unusual chemical reactions impair the metabolism process in the body. This condition affects how the body distributes and processes macronutrients, including protein, lipids, and carbohydrates. Transcription Factor 7 Like 2 (TCF7L2) is a 217,460 bp gene, found in chromosome 10q25, and encodes the High Mobility Group (HMG) box with a role in the Wnt signaling pathway. The Wnt signaling pathway involves several processes during development, healthy homeostasis, and illness. The reactions that follow the pathway's activation regulate both proliferation and differentiation. Single Nucleotide Polymorphism (SNP) in the TCF7L2 gene has been linked to a variety of metabolic disorders incidence. SNP rs11196205 was found to have a significant association with type 1 and type 2 diabetes mellitus, gestational diabetes mellitus, glucose homeostasis, obesity-related parameters, and renal function. Mechanism SNPs causing the metabolic disorder are still unexplained, but SNPs are suspected to affect transcription and splicing processes. SNPs of TCF7L2 genes are reported to affect proinsulin conversion to insulin, decrease incretin hormone production, and decrease insulin sensitivity throughout the body. It can conclude that the screening for the SNP can be a sign of metabolic process abnormalities, especially in diabetes Mellitus.